HOW COVID-19 IS CONTAMINATING THE ECONOMY? - Azouzi, Dhekra (Jurnal Inovasi Ekonomi, 2020)
COVID-19 is spreading around the world, and the number of new cases is being increased daily. We try in this paper to discuss the economic impacts of coronavirus pandemic. Mainly, we cast a glance at the evolution of exchange rates, oil prices, stock indices, and GDP. In conclusion, we highlight the main threats that governments are facing in their fight against this virulent virus and the efforts needed to win this bio-warfare.